2007
DOI: 10.4161/cbt.6.12.4976
|View full text |Cite
|
Sign up to set email alerts
|

PDGF BB induces VEGF secretion in ovarian cancer

Abstract: We identified the platelet derived growth factor receptor (PDGFR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 41 publications
3
51
0
1
Order By: Relevance
“…These signaling ways induces angiogenesis by increasing sprouting, vessel dilation, and the detachment of pericytes from pre-existing vessels, and the subsequent increase in blood supply potently facilitates rapid tumor growth and metastasis 40,41 . These findings make the angiogenic growth factor system an attractive oncologic therapeutic target 42 . In addition, experimental data from several clinical trials suggest the possible benefits of anti-platelet drugs in limiting tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These signaling ways induces angiogenesis by increasing sprouting, vessel dilation, and the detachment of pericytes from pre-existing vessels, and the subsequent increase in blood supply potently facilitates rapid tumor growth and metastasis 40,41 . These findings make the angiogenic growth factor system an attractive oncologic therapeutic target 42 . In addition, experimental data from several clinical trials suggest the possible benefits of anti-platelet drugs in limiting tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experimental data from several clinical trials suggest the possible benefits of anti-platelet drugs in limiting tumor initiation and progression. Many novel VEGF/VEGFR-targeted inhibitors have been reported to improve the prognosis and survival of patients more than chemotherapy alone does 42 , such as bevacizumab and ramucirumab [43][44][45] . However, when VEGF signaling is blocked, other compensatory angiogenic signaling pathways can regulate tumor angiogenesis, including the PDGF, FGF, and hepatocyte growth factor/Met signaling pathways 46 .…”
Section: Discussionmentioning
confidence: 99%
“…2). [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Several types of cancers, particularly those derived from the ovary, prostate, breast, lung, brain, skin, and bone, express PDGFRa on the malignant cells themselves (Table 1). 22 In 1 experiment in which a human tumor array was probed with a cross-reactive polyclonal rabbit antibody to PDGFRa, PDGFRa expression was noted in approximately 95% of osteosarcomas and chondrosarcomas, in 77% of prostate cancers, in 52% of ovarian cancers, in 65% of breast cancers, and in 51% of lung cancers (N. Loizos, ImClone Systems, unpublished results).…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
“…PDGFs can influence cancer growth and malignant angiogenesis through several mechanisms, including the activation of PDGFRa expressed on cancer cells, stromal fibroblasts, and vascular endothelial cells and by PDGF-induced production of vascular endothelial growth factor (VEGF) by stromal cells. [45][46][47][48][49][50][51][52][53][54][55]57,60 The asterisk indicates that Table 1 required for the development of malignant stroma, 46 a separate study indicated that the induction of PDGF-CC expression in melanoma cells led to accelerated tumor growth through the activation of PDGFRa. 47 In the latter study, the exclusive expression of PDGFRa on cancerassociated stromal fibroblasts illuminated a paracrine mechanism of stromal-regulated melanoma tumor growth.…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
See 1 more Smart Citation